BENEFICENCE IS THE HIGHEST MORAL IMPERATIVE OF A DOCTOR DEALING WITH THE POOR QUALITY OF PATIENT AUTONOMY - Veronica Nadya Puteri Nandifa; Yeremias Jena; Satya Joewana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Doctors need good moral reasoning to solve moral issues that cause dilemmas in decision making. But researches on medical students suggest that there was no significant moral development in four-year length of studies and there was a moral regression instead since the students entered clinical years. The aim of this study is to find out the description about Duration of Study in Medical School and Moral Reasoning among Medical Students.Methods: This is a descriptive study using cross-sectional design. Samples were medical students of Atma Jaya Catholic University of Indonesia which enrolled at the year of 2012 – 2016. Duration of study was determined by the school year and moral reasoning was determined based on the domain of autonomy, beneficence-non maleficence, justice and other contextual features found in 3 vignettes of moral problems.Results: Students class of 2012-2016’s moral reasoning dominantly identified the principle of beneficence and non-maleficence. In vignette 1, autonomy, justice and other contextual features also had a quite high answer percentage. Overall students’ moral reasoning is similar between school year, but there was slight difference in clinical students. There was no difference in moral reasoning between male and female.Conclusion: Medical Students respect the principles of beneficence and non-maleficence. There is a slight difference in moral reasoning between the preclinical and clinical students. There was no difference in moral reasoning between male and female.